1980
DOI: 10.1128/iai.27.1.187-191.1980
|View full text |Cite
|
Sign up to set email alerts
|

Transfer factor: a murine model

Abstract: Transfer factor has been studied extensively in humans, but a satisfactory subprimate model has not been established. Using BALB/c mice immunized with complete Freund adjuvant, we show that a low-molecular-weight substance derived from disrupted spleen cells transferred sensitivity to purified protein derivative (PPD) to recipient nonimmunized BALB/c mice. Transfer was confirmed by footpad swelling to PPD in vivo and by splenic lymphocyte transformation to PPD in vitro. In recipients of transfer factor, an inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…As previously noted, other investigators have demonstrated the specificity of various TF preparations in animal models (9,11,18,21,25). In this study we did not attempt to challenge the mice with other strains of Salmonella after TF administration to determine whether cross-protection existed.…”
Section: Discussionmentioning
confidence: 93%
“…As previously noted, other investigators have demonstrated the specificity of various TF preparations in animal models (9,11,18,21,25). In this study we did not attempt to challenge the mice with other strains of Salmonella after TF administration to determine whether cross-protection existed.…”
Section: Discussionmentioning
confidence: 93%
“…Contrary, in patients with DLE as adjuvant, CD4+ and CD8+ and B lymphocytes stayed within median value with increased NK cells amount after logical situations, including inflammation, autoimmunity, transplantation reactions, asthma and anti-tumour immunity [56,57], enhance local inflammatory reactions and modulate immune system functions [58,59]. This pathway may represent main mechanism of immunomodulatory and immunotherapeutic TF actions described in various models [60]. According to last half century studies DLE or TF determines wide range of possibilities to use but due to TF is complex group of many low molecular weight proteins (more than 200), its precise molecular structure and mechanisms of action have not been elucidated yet, which means different studies might be using different TFs and as such need more comparable research conducted.…”
Section: Discussionmentioning
confidence: 99%
“…One of the substances with immunomodulatory effects is a low-molecular weight dialysable leukocyte extract, originally called transfer factor. This extract was proposed to transfer or support specific immunity (Lawrence, 1955), but subsequently more general immunomodulatory properties of TF were detected and TF was used to improve or bal-ance immunological reactivity in different models and in various species, including humans (Jeter et al, 1954;Lawrence, 1955Lawrence, , 1969Burger et al, 1972;Liburd et al, 1972;Bloom, 1973;Klesius and Fudenberg, 1977;Simon et al, 1977;Williams and Kauffman, 1980;reviewed in Viza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of promising results demonstrating the therapeutic potential of TF in experimental models in mice (Williams and Kauffman, 1980), rats (Liburd et al, 1972), guinea pigs (Burger et al, 1972), dogs (Simon et al, 1977) and cows (Klesius and Fudenberg, 1977), clinical trials to transfer specific immunity yielded variable results (Lawrence, 1969). The research on TF mostly waned, and only a spare data on therapeutic effects of TF has been recently published in patients with cancers (Franco-Molina et al, 2008;Lara et al, 2010) and varicella zoster virus infections (Estrada-Parra et al, 1998), in experimental pulmonary tuberculosis (Fabre et al, 2004) and in some other infectious diseases, as recently reviewed by Viza et al (2013).…”
Section: Introductionmentioning
confidence: 99%